The Association Between Dietary Pattern, Physical Activity, Sedentary Activity And Overweight at SMA Negeri 5 Surabaya - Wismoyo Nugraha Putra (Jurnal Berkala Epidemiologi, 2017)
Overweight is a disorder or disease due to an imbalance between incoming and outgoing energy so that it becomes a heap of excessive fat tissue in the body. Some factors that cause overweight include eating patterns, physical activity, and a sedentary lifestyle. This study aims to analyze the relationship between diet, physical activity, and sedentary lifestyle with overweight in 5th Public Senior High School Surabaya. This research is an observational analytic study with a cross-sectional design. The population in this study was 679 students consisting of students of class X-XI. The sample size in this study was 157 students taken by simple random sampling. Data processing using computer applications with univariate and bivariate analysis. The results of the study used chi-square analysis with α = 0.05. The results showed that there was a relationship between sex (p = 0.041), mother's work (p = 0.025), diet (p = 0.035) and physical activity (p = 0.015) with overweight. There is no relationship between parental education, father's occupation, parental income, respondent's allowance, and a sedentary lifestyle overweight Suggestions for schools to hold morning gymnastics together twice a week, and increase the duration of extracurricular activities. Students are expected to be able to increase their consumption of diverse and nutritionally balanced foods.